Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina) - Ruiz, Gustavo R.s.; Bustamante, Abel A. (Zootaxa, 2016)
Edwardsya gen. nov. is proposed to include the type species Attus simoni Taczanowski, 1871 from lower Amazon River, and E. igapo sp. nov. from upper Amazon River, both known only from Brazil. The male of Edwardsya simoni comb. nov. is redescribed and the correct female is described for the first time. Both sexes of the second species are described and illustrated. A modified endite apophysis is described, and a stimulatory role in copulation is proposed for it.